Overview of the Ankle Brachial Index Value of Patients with Type II Diabetes Mellitus at Santa Elisabeth Hospital Medan 2025 - Indra Hizkia Perangin-angin; Rusmauli Lumban Gaol; Magda Sirongo-ringo; Ruliana Br Manalu (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
Type II Diabetes Mellitus is one of the chronic diseases whose prevalence continues to increase and has become a global health issue. A common complication in patients with Type II Diabetes Mellitus is peripheral circulatory disorders, which can be identified through the Ankle Brachial Index (ABI) examination—a non-invasive method used to detect peripheral artery disease. ABI testing is essential for early detection and prevention of serious complications such as diabetic ulcers.This study aims to describe the Ankle Brachial Index values in patients with Type II Diabetes Mellitus at Santa Elisabeth Hospital Medan in 2025. This research used a descriptive quantitative method with purposive sampling technique. The study sample consisted of 52 respondents from a total population of 109 patients diagnosed with Type II Diabetes Mellitus. Data collection was conducted through observation sheets and measurement of systolic blood pressure in the upper and lower extremities using a sphygmomanometer and stethoscope. The ABI value was calculated based on the ratio between the highest ankle systolic pressure and the highest brachial systolic pressure. Data were analyzed using tabulation techniques and presented in tables and diagrams. The results showed that the majority of respondents had normal ABI values (>0.90), totaling 33 individuals (63.5%), while 19 individuals (36.5%) experienced abnormal ABI values (≤0.90).Conclusion:The study concludes that most patients with Type II Diabetes Mellitus at Santa Elisabeth Hospital Medan had ABI values within the normal range. However, a considerable proportion with abnormal ABI indicates the necessity of routine ABI screening as a preventive measure against peripheral vascular complications in diabetic patients. This study is expected to serve as a reference in developing nursing interventions aimed at improving the quality of life for patients with Type II Diabetes Mellitus.